Scientific Approach Assisted by Three-Dimensional Puzzle Media on The Interest and Achievement of Mathematics Learning of Grade V Elementary School Students - Misrini; I Made Ardana; I Nengah Suastika (Jurnal Ilmiah Sekolah Dasar, 2026)
Low learning interest and mathematics achievement among elementary school students remain critical issues, particularly in abstract topics such as geometric nets. This condition indicates that conventional instructional practices have not optimally fostered students’ cognitive engagement and affective involvement simultaneously. This study aims to analyze and examine the effect of a Scientific Approach assisted by three-dimensional puzzle media on students’ learning interest and mathematics achievement. A quasi-experimental design employing a non-equivalent pretest–posttest control group design was implemented. Data were collected through a learning interest questionnaire and an achievement test, and were analyzed using descriptive and inferential statistics, including MANOVA and ANOVA. The findings reveal that the implementation of the Scientific Approach supported by three-dimensional puzzle media significantly enhances and simultaneously influences both learning interest and mathematics achievement. The integration of scientific inquiry processes with concrete manipulative media promotes active engagement, strengthens conceptual understanding, and facilitates meaningful learning experiences. These findings underscore the importance of interactive and exploratory instructional strategies in improving the quality of mathematics learning at the elementary school level.